PENGARUH AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA SEKOLAH (APBS) TERHADAP PARTISIPASI KOMITE SEKOLAH (STUDI EMPIRIS PADA SEKOLAH DASAR NEGERI SE-KECAMATAN PATRANG KABUPATEN JEMBER) - Mahendrati Dwiharja, Laksmi; Kurrohman, Taufik (Jurnal Riset Akuntansi dan Keuangan, 2013)
Accountability and transparency are needed to create credibility and fulfill the principles of good governance. The availability of space for the school committee to get involved is a hallmark of accountability and transparency of educational entities. Lack of accountability and transparency in management of School Budget are factors that affects the participation of school committees on performing the functions and its role against education. The purpose of this study was to examine the effect of accountability and transparency in the management of APBS against participation of the school committee. The population of this research is the Primary School in Patrang, Jember`s Sub District listed in UPT District of Patrang, Department of Education in 2013 year. The sampling method used was purposive sampling, as the school committee to perform its functions more than one year with an error rate of 5% was its basic. Data were collected by trough questionnaires targeted to the school committee involved Chairman, Secretary, Treasurer, and members of structural discretion in each school. The data prior to analysis have been tested for validity and reliability. Techniques of data analysis used multiple regression. Results of this study concludes that accountability and transparency APBS has positive influence significantly on the participation of school committees.